2010
DOI: 10.1016/j.echo.2010.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Survival in Primary Systemic (AL) Amyloidosis, Including Cardiac Biomarkers and Left Ventricular Strain Imaging: An Observational Cohort Study

Abstract: Background The prognostic value of Doppler myocardial imaging, including myocardial velocity imaging, strain, and strain rate imaging, in patients with primary (AL) amyloidosis is uncertain. The aim of this longitudinal study was to identify independent predictors of survival, comparing clinical data, hematologic and cardiac biomarkers, and standard echocardiographic and Doppler myocardial imaging measures in a cohort of patients with AL amyloidosis. Methods A total of 249 consecutive patients with AL amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 21 publications
4
63
4
1
Order By: Relevance
“…Similar findings have been observed in previous studies (3,8,11). Liu et al (11) assessed the incidence of PE in patients with cardiac amyloidosis and showed that the incidence of PE in decompensated heart failure patients was significantly higher than that in compensated patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar findings have been observed in previous studies (3,8,11). Liu et al (11) assessed the incidence of PE in patients with cardiac amyloidosis and showed that the incidence of PE in decompensated heart failure patients was significantly higher than that in compensated patients.…”
Section: Discussionsupporting
confidence: 78%
“…Left and right ventricular (RV) functions assessed by conventional and advanced echocardiography [e.g., tissue Doppler echocardiography (TDE) and speckle tracking echocardiography] and cardiac biomarkers, such as cardiac troponin and brain natriuretic peptide (BNP), have been shown to be strong predictors of mortality in patients with AL amyloidosis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the majority of previous studies have been conducted in Western countries (3)(4)(5)(6)(7)(8)(9)(10)(11), and the predictors of mortality in Asian patients with AL amyloidosis have not yet been characterized (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Their use has been validated in patients treated with conventional 23,36-38 and high-dose chemotherapy. 36,39 In the 2010 consensus analyses, biomarker criteria for clinical cardiac response and progression after initial therapy have been validated in newly diagnosed patients as shown in Figure 2. This approach is a major achievement in the scoring of cardiac responses, considering that these biomarkers are easily available in all clinical chemistry laboratories and that they are well standardized worldwide.…”
Section: Organmentioning
confidence: 99%
“…55 Multivariate analysis identified NYHA class III or IV, presence of pleural effusion, brain natriuretic peptide level >493 pg/ml, ejection time <273 ms, and peak longitudinal systolic basal anteroseptal strain ≥−7.5% as poor independent predictors of clinical outcome in these patients. The mean basal LV longitudinal strain was reported to be a powerful predictor of clinical outcome and was superior to standard 2D echocardiographic, Doppler flow measurements, and simple tissue velocity indices.…”
Section: Strain Doppler Imaging As a Prognosticatormentioning
confidence: 99%
“…Peak systolic strain rate and systolic strain could detect impaired LV systolic function in AL amyloidosis patients with no evidence of cardiac involvement by standard 2D and Doppler echocardiography Strain Doppler imaging as a prognostic factor Bellavia et al 55 …”
Section: (Al)mentioning
confidence: 99%